The Effect of Principal Leadership and Teacher Work Spirit on Teacher Discipline in Elementary Schools - Ofrita, Leni; Kartikowati, Sri; Sumarno, Sumarno (Universitas Riau, 2022)
This study aims to analyze the influence of principals' leadership and teacher morale, either partially or simultaneously, on the discipline of elementary school teachers in Cluster XII, Dumai. The population of this study were all elementary school teachers in the Gugus XII area of Dumai Timur with a total sample of 92 respondents. Determination of the sample using the Probability Sampling technique. The data obtained were then analyzed descriptively. The results of the study indicate that (1) There is a positive and significant influence of principal's leadership on teacher discipline. The better the principal's leadership, the more teacher discipline will increase. (2) There is a positive and significant effect of teacher work spirit on teacher discipline. The higher the work spirit of the teacher, the more the discipline of the teacher increases. (3) There is a positive and significant influence on the leadership of the principal and the work spirit of the teacher together (simultaneously) on teacher discipline. The better the leadership of the principal and the higher the work spirit of the teacher, the better the discipline of elementary school teachers in Cluster XII, Dumai Timur.